Homogeneity, transport, and signal properties of single ag particles studied by single-molecule surface-enhanced resonance raman scattering - Eggeling, C; Schaffer, J; Seidel, C; Korte, J; Brehm, G; Schneider, S; Schrof, W (2001)
We extended the sensitivity of Raman correlation spectroscopy in solution to the single-molecule level by applying surface- and resonance-enhanced Raman scattering (SERRS) combined with time-gated, confocal signal detection. The brightness of the SERRS signal of single Rhodamine 6G molecules adsorbed on a single silver nanoparticle is comparable to fluorescence. Rare event analysis reveals the existence of few particles with simultaneous SERRS and fluorescence signal. The observation of a dynamic exchange between heterogeneous binding sites is supported by the existence of multiple SERRS brightnesses in the signal intensity distribution and by signal fluctuations in the 60 μs time range detected by autocorrelation analysis. Finally, polarization-dependent SERRS autocorrelation curves and single-particle analysis allowed us to measure individual rotational diffusion times and to directly analyze the heterogeneity of the ensemble in solution. © 2001 American Chemical Society.